Análisis y simulación de VSC's con modulación PWM para uso en sistemas HVDC - Peña Suesca, Rafael Antonio; Trujillo Rodríguez, César Leonardo (Ingeniería, 2005)
A High Voltage Direct Current Transmission system (HVDC) requires of electronic converters by its characteristic to turn electrical AC energy in DC energy or vice versa . Basically exist two types of possible configurations of three-phase converters for this process of conversion: Current Source Converter (CSC) and Voltaje Source Converter (VSC).In the present paper will be analyzed threephase converters VSC with modulation PWM, the balance of active power and reactive power, the asynchronous interconnection of three-phase systems with VSC converters and the sizing of some elements of the part of power, using the SimPowerSystems of MatLab®.